Enhanced Acrylic Acid Production via Liquid-Phase Glycerol Oxydehydration Using SBA-15 Supported Heteropoly Phosphotungstic Acid Catalysts: Experimental Evaluation, Mechanistic Understanding, and Kinetic Modelling - Muhammad Yusri, Ahmad; Syamima Nasrin, Mohamed Saleh; Anwar, Ul-Hamid; Ahmad Zuhairi, Abdullah (Springer Nature, 2025)
The expansion of the oleochemical industry results in excess glycerol production to the extent it is regarded as a waste. This drives the exploration of value-added products like acrylic acid to address the surplus and associated environmental issues. However, current processes mainly focus on the gaseous phase, requiring high temperatures and complex setups. Although some research delves into liquid-phase glycerol oxydehydration, information remains limited. In this study, SBA-15 supported heteropoly phosphotungstic acid (HPW) catalysts (PW/SBA-15) with varied acid loadings (10–40 wt %) were synthesized for a single-step liquid-phase glycerol oxydehydration. The impact of calcination temperatures (400–700°C) on catalyst properties and activity was explored. Extensive characterization techniques were employed to assess surface, morphological, and structural properties. Optimal conditions were identified: 3 h reaction time, 240°C reaction temperature, and 10 wt % catalyst loading, achieving 98.7% glycerol conversion and 22.5% acrylic acid yield. Glycerol oxydehydration followed a pseudo second-order kinetic model with an activation energy of 134.4 kJ/mol. The 30PW/SBA-15 catalyst exhibited a defined structure, effectively catalyzing glycerol-to-acrylic acid oxydehydration due to strong acid sites and appropriate redox sites.